Free to lose : an introduction to Marxist economic philosophy - Roemer, John E. (Harvard University Press, 1988)
John Roemer challenges the morality of an economic system based on the private ownership of the means of production. Unless you start with a certain amount of wealth in such a society, you are only "free to lose." This book addresses crucial questions of political philosophy and normative economics in terms understandable by readers with a minimal knowledge of economics.